1978
DOI: 10.1126/science.628838
|View full text |Cite
|
Sign up to set email alerts
|

Cat Color Vision: The Effect of Stimulus Size

Abstract: Adult cats were trained to discriminate blue from green and gray. Although the cats could discriminate the intensity of stimuli whose areas ranged from 33 to 0.36 square centimeters they could not discriminate color when the stimulus was 0.36 square centimeter (less than 20 degrees visual angle). This influence of stimulus size may account for both positive and negative results of previous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2

Year Published

1979
1979
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
5
2
Order By: Relevance
“…The percieved colour was shifted towards the complementary hue by coloured surroundings. In contrast to the findings in cat (Loop & Bruce, 1978) the target size had only a slight influence on perception. Furthermore, the interaction between rods and cones may improve the colour sensitivity of the visual system of man (Reitner et al, 1991).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The percieved colour was shifted towards the complementary hue by coloured surroundings. In contrast to the findings in cat (Loop & Bruce, 1978) the target size had only a slight influence on perception. Furthermore, the interaction between rods and cones may improve the colour sensitivity of the visual system of man (Reitner et al, 1991).…”
Section: Discussioncontrasting
confidence: 99%
“…However, existence of a third cone-type, being sensitive around 500 nm or 600 nm, remains anaissue of discussion (Zrenner & Wienrich, 1981;Ringo et al, 1977). It has been also argued that the visual angle of the deterministic stimulus is decisively influencing the spectral sensitivity of cats (Loop & Bruce, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…This suggests a dichromatism under usual test conditions similar to that of the cat. Until saturated (and large, as suggested by Loop and Bruce [1978]) stimulus lights are used, the possibility of weak trichromatic discrimination by the cat at photopic levels cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…This reaffirmed the existence of a second cone mechanism in the cat. A partial explanation of the difficulty in training cats to make wavelength discrimination has been furnished by Loop and Bruce (1978), who showed that cats very quickly and easily learn wavelength-discrimination tasks when stimulus spots were large. They concluded that the difficulties encountered in earlier behavioral testing resulted from the use of small stimulus spots.…”
Section: Introductionmentioning
confidence: 99%
“…(Loop & Bruce, 1978;Ringo, Wolbarsht, Wagner, Crocker, & Amthor, 1977) may even force us to abandon this notion. In many other respects, cat and human vision are comparable.…”
Section: Outcomementioning
confidence: 99%